Proses Belajar IPA di Madrasah Ibtidaiyah (MI) Yang Efektif Untuk Siswa - Maipah (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
Learning in the classroom is the spearhead of all educational activities conducted by teachers. The purpose of learning is the development of three aspects of competence, namely knowledge, skills, and attitudes, which are obtained in one or more lessons. Teacher’s success in learning is influenced by several aspects. One of them is teacher performance in learning. The ability of teachers in learning is as an absolute requirement that must be met to improve the quality of learning. And students’ learning success is largely determined by the activity of students in the learning process which is created by the teacher. This research is a qualitative research with a literature study that uses books and other literatures as the main object. In this study using data analysis techniques in the form of content analysis. Analysis is a scientific analysis of the message content of a data as analytical and comparative material. In learning science, teachers should use various facilities and learning resources which are oriented to process skills by having observations and research so that students will be contribute actively and creative to find a concept in science. By doing them, students become active and it will be fun to learn science.